Gene Targeting of Components of the Fibrinolytic System - Ploplis, Victoria A.; Castellino, Francis J. (Thrombosis and Haemostasis, 2002)
A number of in vitro and in vivo observations have implicated components of the fibrinolytic system in events associated with diverse physiological and pathophysiological processes, ranging from embryo implantation to cancer. Advances in gene targeting technology have led to the generation of mice deficient for components of the fibrinolytic system. Remarkably, these animals survive to adulthood with few spontaneous life threatening events. Thus, these mice are valuable resources for in vivo studies, not only for hemostasis-related research, but also for the relationships of these genes to other disease states associated with cellular growth and mobility, along with angiogenesis, vascular remodeling, inflammation, wound healing, and tumor growth and dissemination.
Keywords: Gene deficiencies; fibrinolysis; hemostasis; blood